Attitudes towards LGBT in Malaysia : Insights from questionnaires versus interviews. - Hsin-Nie, Ling; Ting, Su Hie (2022)
Lesbian, gay, bisexual, and transgender (LGBT) is considered a sexual minority group in relation to heterosexuals which form the majority in the society. Throughout the years, LGBT individuals have experienced discrimination and negative stigma due to their sexual orientation and gender identity (Buyantueva, 2018). For instance, in Turkey, Yilmaz, and Gocmen (2016) found that LGBT individuals who were discriminated have experienced negative consequences such as dropping out of school, inability to perform in their own profession, and even suffering trauma due to “conversion therapy”. Moreover, LGBT individuals continue to face harassment even in Philippines which is considered as a gay-friendly country, and it is mainly due to the lack of legal protection and religious teachings – mainly Roman Catholic which is against LGBT practice (Tang & Poudel, 2018). Many past researchers have investigated attitudes towards LGBT individuals in colleges and universities (Copp & Koehler, 2017), workplaces (Resnick & Galupo, 2018), and in the health care setting (Naal et al., 2019). Reyes et al. (2019) examined whether religiosity and gender role beliefs influence attitudes toward lesbians and gay men among 633 non-LGBT Filipinos. The findings showed a significant relationship where higher religiosity and more traditional gender role beliefs are associated with more negative attitudes toward lesbians and gay men among the Filipinos participants. In Malaysia, most of the people do not see unconventional sexuality as a norm due to the conservative ideology that being heterosexuals is normal. Tan et al. (2021) reviewed 44 studies on LGBTQ in Malaysia from 1998 to 2020, which involved both quantitative analyses and qualitative interviews. Tan et al.’s (2021) review showed that most of the studies focussed on men who have sex with men (MSM) (Burch et al., 2018), trans women (Galka et al., 2020; Rutledge et al., 2018), and gay men (Felix, 2014; Liow et al., 2017). The researchers either collected data using questionnaires or interviews, but not both. The use of different data collection techniques has been found to influence results in school choice studies where ethnicity is a factor (Bagley, 1996; Elacqua, Schneider, & Buckley, 2006), but it is not known whether the different means of eliciting data would affect results in LGBT studies. This study employed a mixed method research design, using both questionnaire and interviews to examine the Malaysians’ attitudes towards LGBT individuals. The questionnaire data were from 413 respondents (88.1% heterosexuals, 11.9% LGBTs) and a majority of them were aged 21 to 30 (82.3%). Also, a majority of the respondents identified themselves as Chinese (71.7%), 18.6% identified as Malay, 4.6% identified as Sarawak indigenous, 2.2% identified as Indian, and 1.2% identified as Sabah indigenous. The interview data were from 20 participants (14 heterosexuals and six LGBT). The distribution of religious background is as follows: Muslim (45.0%), Christians (25.0%), Buddhists (10.0%), Others (5.0%). The questionnaire elicited data on four main constructs (tolerance towards LGBT individuals, 13 items), social knowledge on morality (9 items), tolerance towards social interaction with LGBT individuals, 10 items), and intergroup contact with LGBTs (11 items), using a seven-point Likert scale. The interview guide elicited the heterosexuals’ attitudes towards LGBT and the LGBT participants’ experiences in disclosing their identity. The quantitative data were collected through the distribution of Google Forms link to first author’s social network. Respondents answered the questionnaire after they had given consent. For the interviews, the researcher first contacted eligible heterosexual respondents and interviewed them. After that, researcher requested help from heterosexual respondents to recruit LGBT respondents, mainly their acquaintances, to take part in the interviews. Quantitative data were analysed using SPSS Version 26.0 and qualitative data were analysed using discourse-historical approach (DHA) proposed by Reisigl and Wodak (2009). The results from both data were then compared to examine whether discursive strategies used by respondents to talk about LGBTs reflect their self-reported attitudes towards LGBTs too. The questionnaire and interview results were compared on three points, namely, nature versus nurture, rights, and acceptable social roles for LGBT individuals. Firstly, the questionnaire results showed mixed responses on whether LGBT is nature or nurture, but the interviews revealed that heterosexual participants mostly agreed that being LGBT is a personal choice due to environmental influence such as upbringing and social media. On the other hand, the LGBT participants felt that it is a natural kind of expression and they cannot change their sexual orientation. Therefore, most of them would disagree with heterosexuals who advise them to change their sexual orientation. Secondly, on the LGBT rights construct, the self-reported questionnaire results showed that a majority of the participants agreed that LGBT individuals deserve all kinds of rights in the society including getting married legally and adopting children. However, the interview results showed that heterosexuals expressed a range of attitudes, from disagreement to neutrality and agreement, on the idea of legalizing same-sex marriage. In other words, there was more granularity in the interview results, compared to questionnaire responses which were subject to social desirability bias – with the participants wanting to appear as if they support human rights and were open to LGBT. Thirdly, on the acceptable social roles for LGBT individuals, the questionnaire results and interview results were similar. The questionnaire results showed that a majority of the participants can accept LGBTs in most of the social roles, including friends, neighbors, teachers, military officers, and colleagues. The interview results for the heterosexual participants were similar to the questionnaire results in that they could not accept it if their religious leaders and their own children were to be LGBT. Because of this, the LGBT participants interviewed in this study were afraid to disclose their sexual orientation to their parents because they knew that their parents would not able to accept them. From the interviews, it is clear that the first group of people that LGBT participants would come out to is their friends, but only selected friends. The LGBT participants felt the acceptance from their heterosexual friends and colleagues even after they have come out from the closet. In conclusion, the study showed that for LGBT studies, the data collection technique does not substantially influence results. This result is important because it means that questionnaires can be used to study attitudes towards LGBT on a large scale, and still capture the key patterns. The only difference is that interviews enable researchers to attain a more in-depth understanding of the thoughts, beliefs and experiences that underlie the professed or reported attitudes towards LGBT.